2009
DOI: 10.1002/cmdc.200900386
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Optimisation in Drug Discovery: A Case Study using Carbonic Anhydrase Inhibitors

Abstract: Historically the early stages of drug discovery have been based on finding the highest affinity compounds that bind to the target of interest, with little consideration for the forces driving the binding event. The association constant (K a ) can be defined by the equation DG = ÀRTln K a , with DG = DHÀTDS. To fully describe K a it would therefore be beneficial to characterize both of the thermodynamic terms (DH and DS) that drive this affinity for binding. The importance of separating affinity into its thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 21 publications
7
82
0
1
Order By: Relevance
“…Our results demonstrate the same trend for BPs: newer, more potent drugs are enthalpically more optimized. Altogether, as has been suggested previously, [29][30][31]33,40) our results argue the importance of monitoring thermodynamics balance of the drug/target interaction to efficiently produce best-in-class compounds.…”
Section: )supporting
confidence: 84%
See 1 more Smart Citation
“…Our results demonstrate the same trend for BPs: newer, more potent drugs are enthalpically more optimized. Altogether, as has been suggested previously, [29][30][31]33,40) our results argue the importance of monitoring thermodynamics balance of the drug/target interaction to efficiently produce best-in-class compounds.…”
Section: )supporting
confidence: 84%
“…27,28) Such thermodynamic profiles of the binding are helpful in drug discovery. [29][30][31][32][33] Recent studies have also suggested the importance of enthalpy-driven optimization when exploring drug candidates. 29) For example, Freire et al have examined the complete thermodynamics information of two drug classes: statins and human immunodeficiency virus-1 (HIV-1) protease inhibitors.…”
mentioning
confidence: 99%
“…Inhibition effects of the compounds (3,4-diamino-benzenesulfonamide 1, 3-amino-4-chlorobenzenesulfonamide 2, 5-amino-2-methylbenzenesulfonamide 3, and acetazolamide 4) on SUMO fusion the wt and mutant enzymes were analyzed in their different concentrations. The Cheng-Prusoff equation was used to determine the K i values of each compound (Scott et al, 2009). …”
Section: Hca II Inhibition Experimentsmentioning
confidence: 99%
“…Owing to their low affinity, compounds have to be screened at high concentration that requires high solubility. In line with their small size and polarity that allows fragments to form few, good quality polar interactions without significant contribution from apolar desolvation fragment hits typically bind with favorable enthalpy [17,30,31,32,33,34,35] ( Figure 5). The few compounds in Figure 5 that bind with unfavorable enthalpy are all anionic species with highly unfavourable desolvation profile.…”
Section:  Thermodynamic Rationale Of Fragment Based Approachesmentioning
confidence: 99%